Pendidikan Karakter Dalam Era Digital: Bagaimana Teknologi Mempengaruhi Pembentukan Moral Dan Etika - Fitri Aulia Rahman; Miftakhul Rohmah; Sentit Rustiani; Icha Yuniaris Fatmawati; Novem Alisda Dewi Sofianatul Zahro (Pusat Riset dan Inovasi Nasional, 2023)
This research is motivated by the increasing decline in morals and ethics in society due to the increasing development of technology in the world. Where the content contained in it greatly influences the formation of people's character. Therefore, this research was carried out so that people can be wiser in using social media and not view social media as something trivial and its existence does not need to be paid attention to in forming children's character. The objectives to be achieved in this research are a. the influence of social media in character formation, especially in morals and ethics in the digital era b. necessary solutions in dealing with the influence of social media in character formation, especially in terms of morals and ethics in the current digital era. This research was conducted on students attending high school level with an age range of 16-18 years. The results of this research prove that social media is very influential on the formation of student character which includes the morals and ethics of students and this research also proves that social media is very closely related to students and is very difficult to separate, but social media is also like a double-edged sword. for students because if they cannot use it well then they will fall in the wrong direction which will cause their morals and ethics to decline and if they can use it well then they will have a wide network in society. The method used in this research is the Creswell case study qualitative research method by digging deeper into character education in the digital era: how technology influences the formation of morals and ethics so that we can find out more deeply about the influence of technology in the formation of morals and ethics in the digital era and its challenges. challenges faced and ultimately lead to finding solutions to the challenges and problems faced in character formation in the digital era. Based on the research we conducted, we also obtained several solutions to deal with the influence of social media in character formation by using platforms that are familiar to students to deliver character education and then providing students with an understanding of how to use social media wisely.